Overexpression of glutathione peroxidase-1 attenuates cocaine-induced reproductive dysfunction in male mice by inhibiting nuclear factor κB. (1st July 2019) - Mai, Huynh Nhu; Chung, Yoon Hee; Shin, Eun-Joo; Jeong, Ji Hoon; Jung, Tae Woo; Sharma, Naveen; Lei, Xin Gen; Nah, Seung-Yeol; Jang, Choon-Gon; Kim, Dae-Joong; Yang, Boo-Keun; Kim, Hyoung-Chun
Abstract: Since reproductive toxicity is associated with oxidative stress, nuclear factor κB (NFκB), a redox-sensitive transcription factor, may be involved in the reproductive dysfunction induced by the abusive drug, such as cocaine. In the present study, we investigated whether NFκB mediates cocaine-induced reproductive dysfunction in male mice, and whether glutathione peroxidase (GPx)-1, a well-known enzymatic antioxidant, modulates NFκB activity to affect this reproductive dysfunction. Cocaine treatment significantly increased nuclear translocation of NFκB and its DNA binding activity in the testis of mice. Treatment with cocaine resulted in a significant increase in sperm abnormality, and in significant decreases in the sperm viability and sperm level. Furthermore, cocaine significantly reduced hypothalamic gonadotropin-releasing-hormone expression and plasma testosterone level. These alterations were more pronounced in the GPx-1 knockout (GPx-1 KO) than wild type (WT) mice, and they were less pronounced in GPx-1 overexpressing transgenic (GPx-1 TG) than in non-transgenic (non-TG) mice. Pyrrolidine dithiocarbamate (PDTC), an NFκB inhibitor, was more effective in attenuating cocaine-induced reproductive toxicity in GPx-1 KO than in WT mice. Although PDTC treatment was also significantly protective against the reproductive toxicity in non-TG mice, PDTC did not show additional positive effects against the protective potential mediated by GPx-1 overexpression in mice. Therefore, our results suggest that GPx-1 gene is a protective factor in response to reproductive dysfunction induced by cocaine in male mice, and that NFκB is a critical mediator of protective activity of GPx-1 gene in our experimental conditions. Graphical abstract: Image 1 Highlights: Prolonged cocaine treatment induced c-Fos and oxidative stress in mouse testis. Cocaine treatment compensatively induced GPx-1, and increased NFkB in the testis. Cocaine reproductive dysfunction was ameliorated by NFkB inhibition or GPx-1 gene. Genetic depletion of GPx-1 augmented cocaine-induced reproductive dysfunction.